PERSEMBAHAN JEMAAT : Konsep Teologis dan Implementasi Praktis - Natalia, Fiska; Purwanto, Purwanto (STT KINGDOM BALI, 2025)
Giving offerings is a form of expression of gratitude, a sign of atonement for wrongdoing, and a sign of salvation to God. Christians express gratitude to God for all the blessings that God has given, so there are offerings. Since Sunday school they have been taught to make offerings, namely giving some of their possessions in the form of material things or money. Offerings are not only about money but also our service in the church, helping others, loving as God loves us are also forms of offering. The method used in this research is a qualitative method with a descriptive approach. The qualitative research method is field research by collecting data directly in the field, engaging with the community and sharing what we feel, we must evangelize it so that many souls are saved, not just Christians but all nations so that Jesus' mission can be made easier for them. feel and get a picture that we have to show God's love which is irresistible to all mankind, often churches only want to develop their people if only Christians are evangelized, pity those of other religions who still don't believe, still living in our attachments as won souls.